Model for Sustainability Improvement of Student Satisfaction Based on Service Quality: Testing the American Customer Satisfaction Model in Higher Education - Raharjo, Teguh Hardi; Ismiyati, Ismiyati; Ikhsananto, Aan (Dinamika Pendidikan, 2024)
This research aims to empirically investigate the antecedents and consequences of student satisfaction with programs provided by higher education institutions and identify service quality attributes that need to be improved. This research uses the American Customer Satisfaction Model (ACSM) as an analytical lens. The unit of analysis in this research concentrates on students who are studying at Semarang City Universities. Partial Least Squares (PLS) estimation is used to test measurement models, estimate the predictive power of theoretical models, and obtain the SSI score. Although student satisfaction is a complex concept, this model has proven to be an accurate estimator. The research results show that student satisfaction is entirely satisfactory, with an SSI score of 68.75. Through the Structural Measurement Method, it was found that perceived benefits and interactions in the process had the most significant influence on satisfaction. This research contributes to discussions about service quality by highlighting the role of perceived usefulness and aspects of the interaction process as factors shaping service quality. Apart from that, this research also reinforces the discussion regarding the relationship between student satisfaction and complaints by showing that this relationship is negative if managed by producing graduates loyal to the university.